PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TPS SECARA DARING TERHADAP HASIL BELAJAR KOGNITIF PESERTA DIDIK PADA MATERI LARUTAN PENYANGGA - Manuella Tandi Toding; Dian Oktavia Pandi (Universitas Papua, Manokwari, Indonesia, 2021)
Abstract Chemistry learning in class requires a learning model that evokes the activeness of students, one of which is the Think Pair Share (TPS) cooperative learning model which is a learning model that gives students time to think and respond and help each other. This study aims to determine the difference in the effect of using the online Think Pair Share (TPS) learning model on the cognitive learning outcomes of students in class XI IPA 2 SMA YPK Oikoumene Manokwari on the material of the buffer solution. The research method used a pretest-posttest control groub design. The sampling technique used purposive sampling. Data collection tools in the form of observation, interviews, learning outcomes tests, and documentation. The data analysis used is descriptive analysis and inferential analysis with the help of SPSS 26 software. Based on the results of data analysis, it can be concluded that the Sig (2-tailed) value is 0,000 <0,025, then Ha is accepted and H0 is rejected so that there is a significant difference in cognitive learning outcomes. students from the use of the Think Pair Share (TPS) learning model of class XI IPA 2 and the conventional model of class XI IPA 1 with the percentage of the effect of 57%. Keywords: Learning, Students, Think Pair Share (TPS), Learning Outcomes